Factors Associated with Medication Adherence among Patients in the Back-Referral Program (PRB) - Ummu Khadijah; Sunandar Said; Mardhatillah Mardhatillah; Pratiwi Ramlan (Sarana Ilmu Indonesia (salnesia), 2026)
Medication adherence among patients with chronic diseases remains a global health problem, characterized by low adherence rates that contribute to increased complications and healthcare costs. In Indonesia, the Referral Back Program (Program Rujuk Balik/PRB) as a chronic disease management strategy was not optimally implemented, including at the UPT Puskesmas Rappang, where adherence levels were still below the target. This study aimed to analyze factors associated with medication adherence among PRB patients at UPT Puskesmas Rappang, Sidenreng Rappang Regency. A quantitative study with a cross-sectional design was conducted. The population consisted of 156 patients, with 112 subjects selected using simple random sampling. Data were collected through questionnaires and analyzed using the Chi-square test with a significance level of p < 0.05. The results showed that knowledge, access to information, and family support were significantly associated with medication adherence among PRB patients, indicating that these factors play an important role in shaping patient adherence behavior. In conclusion, knowledge, access to information, and family support are significantly related to medication adherence among PRB patients. Therefore, it is recommended that health centers improve continuous health education, expand accessible health information, and actively involve families in supporting patient adherence to long-term treatment.